On dependencies between architecture and media: considering the remote work - Christenson, Mike (Enquiry The ARCC Journal for Architectural Research, 2008)
To consider architecture as a communicative medium requires acknowledgment of the necessity of mediating artifacts suchas drawings, models, and photographs, insofar as these artifacts provide structure for communication and discourse. In this essay, I examine the criticality of mediating artifacts to architecture's communicative potential by proposing a tactical identity between the act of architectural design and the study of architectural precedent. In both situations, mediating artifacts incorporate decisions and assumptions about how architectural significance should be communicated.I propose two hypotheses as frames within which to discuss architecture's dependence on mediating artifacts. First, the Neutral Frame hypothesis suggests that significant attributesof a work of architecture are capable of disclosure regardless of the medium through which these attributes are "filtered.” By contrast, the Production Bias hypothesis holds that significant attributes of a work of architecture can be identified as unique to a medium of investigation, and furthermore, that in some cases it may not be possible to disclose a given attribute by any other means. By considering existing photographs of a completed work of architecture (Crown Hall in Chicago,Illinois) in two ways, first through computer-aided manipulation and second by diagramming superimposed fields-of-view of photographs from two distinct sources, I suggest that the Production Bias hypothesis is the better explanation of architecture's relationship to mediating artifacts.